2014
DOI: 10.3748/wjg.v20.i16.4723
|View full text |Cite
|
Sign up to set email alerts
|

MT1MandMT1Gpromoter methylation as biomarkers for hepatocellular carcinoma

Abstract: MT1M and MT1G promoter methylation may be used as serum biomarkers for noninvasive detection of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 32 publications
3
50
0
1
Order By: Relevance
“…Among these 33 publications, 11 articles described the diagnostic role of circulating Ras association domain family 1 isoform A ( RASSF1A ) methylation in HCC and eight articles evaluated the diagnostic performance of ctDNA combined with AFP assay in HCC . Nine articles assessed the diagnostic accuracy of AFP assay for HCC …”
Section: Resultsmentioning
confidence: 99%
“…Among these 33 publications, 11 articles described the diagnostic role of circulating Ras association domain family 1 isoform A ( RASSF1A ) methylation in HCC and eight articles evaluated the diagnostic performance of ctDNA combined with AFP assay in HCC . Nine articles assessed the diagnostic accuracy of AFP assay for HCC …”
Section: Resultsmentioning
confidence: 99%
“…Previously, other researchers have reported dramatic loss of MT expression in primary human HCC by immunohistochemistry methods . Recently, MT1M promoter methylation was reported as biomarkers for HCC or breast cancer . Majumder's group reported that MT1 and MT2 double knockout accelerates hepatocarcinogenesis in mice exposed to the carcinogen diethylnitrosamine .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Recently, MT1M promoter methylation was reported as biomarkers for HCC or breast cancer. 21,22 Majumder's group reported that MT1 and MT2 double knockout accelerates hepatocarcinogenesis in mice exposed to the carcinogen diethylnitrosamine. 23 Mao's group reported that frequent downregulation of MT1M in human HCC may contribute to liver tumorigenesis by increasing cellular NF-κB activity.…”
Section: Discussionmentioning
confidence: 99%
“…[56] It has been suggested that MT downregulation in cancer is related to promoter hypermethylation as previously shown in hepatoma. [57] It can thus be hypothesized that hypermethylation of the MT promoter may also occur in PCs, leading to a decrease in MT-mediated removal of free radicals, which may cause DNA damage and trigger cancer initiation. However, it has also been shown that MTs contribute to drug resistance in cancers.…”
Section: Resultsmentioning
confidence: 99%